Service Quality and Trust on Customer Satisfaction - Ahmad, Alfina Damayanti S; Akbar, Mohammad Aldrin; Lina, Ros (Advances: Jurnal Ekonomi & Bisnis, 2024)
Purpose: This study aims to determine the relationship between service quality and trust in customer satisfaction of Livin Mandiri users in Jayapura City. Research Design and Methodology: This research methodology uses a quantitative approach. Customers were distributed questionnaires, and the collected data was analyzed using statistical techniques. Findings and Discussion: The research findings show that the main components of service quality—reliability, responsiveness, assurance, empathy, and physical evidence—and elements of trust, such as honesty, credibility, and reliability, significantly affect customer satisfaction. Good service quality creates a solid basis for building confidence, while high trust strengthens customers' perceptions of service quality. Implications: This study's practical implications are that digital banking companies must holistically integrate service quality improvement and trust-building strategies to increase customer satisfaction and loyalty. This research contributes to science by offering a comprehensive framework for analyzing customer satisfaction and demonstrating originality in ana integrated service quality and trust approach.